Effect of Various Herbicides on Warm‐season Grass Weeds and Switchgrass Establishment. Issue 2 (1st March 2013) - Kering, Maru K.; Huo, Chengjun; Interrante, Sindy M.; Hancock, Dennis W.; Butler, Twain J.
ABSTRACT: Switchgrass ( Panicum virgatum L.) is typically slow and difficult to establish. Field experiments evaluated switchgrass establishment and the response of warm‐season grass weeds (large crabgrass [ Digitaria sanguinalis (L.) Scop.], broadleaf signalgrass [ Urochloa platyphylla (Munro ex C. Wright) R.D. Webster], Johnsongrass [ Sorghum halepense (L.) Pers.], and Texas panicum [ Urochloa texana (Buckley) R.D. Webster]) to a preemergence (cloransulam) or postemergence (foramsulfuron, pendimethalin, quinclorac, foramsulfuron + pendimethalin + quinclorac, nicosulfuron, nicosulfuron + pendimethalin + quinclorac, nicosulfuron + quinclorac + atrazine, and monosodium methanearsonate [MSMA]) herbicides. Experimental design was a split‐split‐plot design with presence/absence of preemergence herbicide cloransulam as main plot, weed species as subplot treatment, and postemergence herbicides as sub‐subplot treatments. Herbicides foramsulfuron + pendimethalin + quinclorac was applied at the 1‐ to 2‐ and 2‐ to 3‐leaf stage, whereas nicosulfuron was applied at 2‐ to 3‐leaf stage and nicosulfuron combinations and MSMA were applied at 3‐ to 4‐leaf stage. Using cloransulam as a preemergence herbicide resulted in lower switchgrass seedling numbers and generally did not improve establishment. Interseeding Johnsongrass allowed for the greatest number of switchgrass seedlings and was the least competitive weed, whereas interseeding large crabgrass resulted in the least amount of switchgrass and proved to be the most competitive weed. Foramsulfuron + pendimethalin + quinclorac resulted in effective weed control (>70%) for all four species evaluated and improved switchgrass establishment (13–26%) compared to the untreated control (0–3%); however, greater improvement in stand establishment is needed.